Pengaruh Penggunaan Coretax Terhadap Ketepatan Perhitungan Pajak Dan Tingkat Kesalahan Pelaporan Di Indonesia - resyfifianti; Puji Rahayu (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Digital transformation in the taxation sector has encouraged the Directorate General of Taxes to implement a core tax administration system based on information technology known as Coretax. This system is designed to improve the efficiency, accuracy, and quality of tax administration, particularly in the aspects of tax calculation and reporting. This study aims to analyze the effect of Coretax use on the accuracy of tax calculations and the level of tax reporting errors among corporate taxpayers. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to corporate taxpayers who have used Coretax. Data were analyzed using descriptive statistical analysis and multiple linear regression. The results show that Coretax use has a positive and significant effect on the accuracy of tax calculations, and a negative effect on the level of tax reporting errors. These findings indicate that optimal utilization of the Coretax system can improve the quality of tax administration. This research is expected to provide evaluation material for tax authorities in improving the digital tax system in Indonesia.